Toxic effects of maternal zearalenone exposure on intestinal oxidative stress, barrier function, immunological and morphological changes in rats. - Min Liu (Public Library of Science (PLoS), 2014)
The present study was conducted to investigate the effects of maternal zearalenone (ZEN) exposure on the intestine of pregnant Sprague-Dawley (SD) rats and its offspring. Ninety-six pregnant SD rats were randomly divided into four groups and were fed with diets containing ZEN at concentrations of 0.3 mg/kg, 48.5 mg/kg, 97.6 mg/kg or 146.0 mg/kg from gestation days (GD) 1 to 7. All rats were fed with mycotoxin-free diet until their offspring were weaned at three weeks of age. The small intestinal fragments from pregnant rats at GD8, weaned dams and pups were collected and studied for toxic effects of ZEN on antioxidant status, immune response, expression of junction proteins, and morphology. The results showed that ZEN induced oxidative stress, affected the villous structure and reduced the expression of junction proteins claudin-4, occludin and connexin43 (Cx43) in a dose-dependent manner in pregnant rats. Different effects on the expression of cytokines were also observed both in mRNA and protein levels in these pregnant groups. Ingestion of high levels of ZEN caused irreversible damage in weaned dams, such as oxidative stress, decreased villi hight and low expression of junction proteins and cytokines. Decreased expression of jejunal interleukin-8 (IL-8) and increased expression of gastrointestinal glutathione peroxidase (GPx2) mRNA were detected in weaned offspring, indicating long-term damage caused by maternal ZEN. We also found that the Nrf2 expression both in mRNA and protein levels were up-regulated in the ZEN-treated groups of pregnant dams and the high-dose of ZEN group of weaned dams. The data indicate that modulation of Nrf2-mediated pathway is one of mechanism via which ZEN affects gut wall antioxidant and inflammatory responses.